2019
DOI: 10.3390/jcm8081137
|View full text |Cite
|
Sign up to set email alerts
|

Mortality from Alcoholic Cardiomyopathy: Exploring the Gap between Estimated and Civil Registry Data

Abstract: Background: Based on civil registries, 26,000 people died from alcoholic cardiomyopathy (ACM) in 2015 globally. In the Global Burden of Disease (GBD) 2017 study, garbage coded deaths were redistributed to ACM, resulting in substantially higher ACM mortality estimates (96,669 deaths, 95% confidence interval: 82,812–97,507). We aimed to explore the gap between civil registry and GBD mortality data, accounting for alcohol exposure as a cause of ACM. Methods: ACM mortality rates were obtained from civil registries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 35 publications
(65 reference statements)
0
15
0
1
Order By: Relevance
“…Consequently, our estimates are higher than those by Rosén and Haglund (2019) and by Trias-Llimós et al (2020)-which were only based on causes of death wholly related to alcohol [18,19]-and are lower than estimates that include all deaths from causes of death partly attributable to alcohol (e.g., external causes of death), like the estimates by Pruckner et al (2019) [17]. Secondly, we adapted the GBD alcohol-attributable mortality rates for 65+ in response to quality concerns due to the limitations of applying their estimation technique at higher ages [20,23]. Compared to the very steep increases (men) and steep declines (women) in alcohol-attributable mortality rates with age observed in the GBD data, we obtained an inverted U-shaped curve for both sexes (see Supplementary File 1-Appendix Figure A1), which is considered more realistic [20].…”
Section: Evaluation Of Data and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, our estimates are higher than those by Rosén and Haglund (2019) and by Trias-Llimós et al (2020)-which were only based on causes of death wholly related to alcohol [18,19]-and are lower than estimates that include all deaths from causes of death partly attributable to alcohol (e.g., external causes of death), like the estimates by Pruckner et al (2019) [17]. Secondly, we adapted the GBD alcohol-attributable mortality rates for 65+ in response to quality concerns due to the limitations of applying their estimation technique at higher ages [20,23]. Compared to the very steep increases (men) and steep declines (women) in alcohol-attributable mortality rates with age observed in the GBD data, we obtained an inverted U-shaped curve for both sexes (see Supplementary File 1-Appendix Figure A1), which is considered more realistic [20].…”
Section: Evaluation Of Data and Methodsmentioning
confidence: 99%
“…The GBD estimates of alcohol-attributable mortality for the highest ages (65+) are, however, considered implausible, as they are either very high or negative (e.g., [20,23]). Among the explanations for these potential inaccuracies are that the estimation technique is highly dependent on the limited information on alcohol use at these ages; age-specific relative risks (RRs) of dying are lacking at these ages; and, more generally evidence regarding the impact of alcohol on health at those ages is lacking (e.g., [20,23]).…”
Section: Alcohol-attributable Mortality Estimatesmentioning
confidence: 99%
“…Mortality in ACM is related to the progression of heart failure and malignant arrhythmias [58,65]. In long-term follow-up studies, a mortality rate of 10% of patients/year has been observed in the group of patients with persistent high-dose ethanol consumption [19,52].…”
Section: The Natural Course Of Acmmentioning
confidence: 99%
“…Thirty percent of EMBs of patients with excessive alcohol consumption showed lymphocytic infiltrates with myocyte degeneration and focal myocardial necrosis [ 119 , 120 ]. Based on data from 77 countries, alcoholic cardiomyopathy has been demonstrated in 1.54 billion adults, mainly in American and WHO European Regions [ 121 ].…”
Section: Epidemiology Of Myocarditismentioning
confidence: 99%